Synthesis, Spectroscopy, Antibacterial and Anti-inflammatory Studies of Homo and Hetero Bimetallic Complexes with Bifunctional (O, S) Ligand - Mafia Noreen; Shabbir Hussain; Muhammad Shahid; Shazma Massey; Amina Asghar; Khurram Shahzad Munawar (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2025)
Current studies were performed to synthesize homo- (Sn & Sn) and heteronuclear (Sn & Cd/Zn) complexes (1-7) of sarcosine dithiocarbamate and investigate their antibacterial and anti-inflammatory potential. Homobimetallic products, i.e., Ph2(Cl)SnSSCLSn(Cl)Me2 (1), Ph2(Cl)SnSSCLSn(Cl)Me3 (2), Ph2(Cl)SnSSCLSnBu3 (3) were produced by a reaction of sarcosine (HLH), CS2 and Ph2SnCl2 and then with Me2SnCl2, Me3SnCl and Bu3SnCl, respectively. Ph3SnSSCLSn(Cl)Bu2 (4) and Ph3SnSSCLSnMe3 (5) were produced by reacting HLH with KOH, CS2 and Ph3SnCl firstly and then with Bu2SnCl2 and Me3SnCl, respectively. The heteronuclear products, i.e., (Ph3SnSSCL)2Cd (6) and (Ph3SnSSCL)2Zn (7) were formed by reaction between HLH, KOH, CS2 and Ph3SnCl followed by treatment with CdCl2 or ZnCl2, respectively. Elemental analysis data was agreed well with the molecular composition of the products. Fourier transform infrared (FTIR) spectroscopy have shown the bidentate binding of carboxylate and dithiocarbamate donor sites of ligand. Proton nuclear magnetic resonance (1H NMR) spectroscopy of 3 displayed the expected signals of ligand portion and organotin(IV) moieties. TGA data of product 7 verified its heterobimetallic (2Sn, ZnO) composition. All the products except 4 and 6 exhibited significant antimicrobial activities as compared to free ligand. The highest anti-inflammatory potential was displayed by product 3.